(3GdfLe GdhgGL aj TQM GdefgGLs - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s; (3CHh YHO Gddg eMeO Hf eMeO Hf YHO Gddg Hf JLdGJ GdeQGcTjs
(3ChdgG (B:s
(3haGJM CHhGH GdCUhd hGdVhGHW s
(3BNQgG (B:s
(3hgj WYGe jYed GdbOhe GdeSGaQ hSjCJi ai GdhdjeI HjGfgG fLR GdLRA GdChd ef GdfLe GdhgGL ai TQM GdefgGL s
(3fSNI SGOSIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs